Adverse childhood experiences among Latina women and its association with mastery of stress and health. (July 2019) - Alvarez, Carmen; Perrin, Nancy; Lameiras-Fernandez, Maria; Rodriguez, Rebecca; Glass, Nancy
Abstract: Background: Adverse childhood experience (ACE) and intimate partner violence (IPV) have sustained, deleterious effects on physical and mental health. Few studies have examined how to help Latina survivors of ACEs and/or IPV regain control of their health. Objective: To inform interventions for this population, we examined whether mastery of stress and patient activation mediate the relationship between a history of ACE and/or IPV and mental and physical health. Participants and setting: We recruited 235 Latina women ( M age = 29.6, SD  = 5.75) from primary care clinics. Method: For this cross-sectional study, we used linear regressions to examine the association between ACEs, history of IPV, and health, and the sobel's test to determine whether patient activation and mastery of stress mediated the relationships between ACEs, IPV, and health. Results: Most women reported at least one ACE (61.7%, n = 137) and 22.2% (n = 55) reported a history of IPV. Mastery of stress mediated the relationship between ACE and physical health (b= -3.16 p  = .002) and mental health (b= -3.83, p  <  .001). Mastery of stress also mediated the relationship between history of IPV and physical health (b= -2.62, p  = .008) and mental health (b= -2.74, p  = .006). Patient activation was not associated with a history of trauma or mental health. Conclusion: While past experiences of trauma cannot be changed, results from this study suggest that improving an individual's mastery of stress may be a point of intervention for improving mental and physical health among survivors of ACEs and IPV.